2019
DOI: 10.1017/s1368980019001496
|View full text |Cite
|
Sign up to set email alerts
|

Latent profile analysis of dietary intake in a community-dwelling sample of older Americans

Abstract: Objective:To estimate latent dietary profiles in a community-dwelling sample of older Americans and identify associations between dietary profile membership and individual demographic, socio-economic and health characteristics.Design:Secondary analysis of the 2012 Health and Retirement Study (HRS) and linked 2013 Health Care and Nutrition Study (HCNS). Latent profile analysis identified mutually exclusive subgroups of dietary intake and bivariate analyses examined associations between dietary profile membershi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 33 publications
2
22
1
Order By: Relevance
“…No associations were observed between dietary patterns and age within the current study. Contrasting results have been reported in other studies in an older population [9,10,12,[14][15][16][17][18]. The narrow age band of the REACH study (65 to 74 years) may have precluded observing any associations.…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…No associations were observed between dietary patterns and age within the current study. Contrasting results have been reported in other studies in an older population [9,10,12,[14][15][16][17][18]. The narrow age band of the REACH study (65 to 74 years) may have precluded observing any associations.…”
Section: Discussioncontrasting
confidence: 82%
“…For the studies that have reported the variation explained, the R 2 ranged from 1 to 44% [57][58][59]. Other factors explaining food choice included quality and price of food available, family preferences and taste, trying to eat healthy [60], and physical disability limiting access to food [18,61].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Occupation plays an important role on the quality of the diet [20]. It may be related to income [21], where the consequences for the retired elderly are: there is a decrease in income or even incomeless. In the next stage, they cannot access certain food products [22], including healthy foods according to their needs, physical condition, and age.…”
Section: Occupational Status and Eating Habitsmentioning
confidence: 99%
“…The impact of age on dietary behavior among already older adults is ambiguous, as the results of previous research are partly inconsistent. While age was negatively associated with a “vegetable-based” pattern [ 30 ], no associations were observed between age and a “Mediterranean” pattern [ 19 ], or age and a “healthy” pattern [ 31 ]. In the analysis of age groups, a “healthy” pattern was negatively associated with the 75 years or older age group in the female sample, whereas no association could be found for the 70–74 age group [ 24 ].…”
Section: Introductionmentioning
confidence: 99%